2005
DOI: 10.1007/bf03021607
|View full text |Cite
|
Sign up to set email alerts
|

Successful near-term pregnancy outcome after repair of a dissecting thoracic aortic aneurysm at 14 weeks gestation

Abstract: Aortic dissection in pregnancy may have catastrophic results. Undoubtedly, it presents unique challenges for anesthetic and obstetrical management. With appropriate care and surgical correction of the dissecting aneurysm early in pregnancy, a successful outcome for the pregnancy was possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In case of an urgent need for surgery and to prevent unfavorable fetal outcome, an immediate cesarean section followed by cardiac surgery is recommended. 11,13,18,19,30 …”
Section: Labor and Deliverymentioning
confidence: 99%
“…In case of an urgent need for surgery and to prevent unfavorable fetal outcome, an immediate cesarean section followed by cardiac surgery is recommended. 11,13,18,19,30 …”
Section: Labor and Deliverymentioning
confidence: 99%
“…Previous authors have reported Cesarean deliveries in women with Marfan's syndrome under general [5][6][7] and neuraxial anesthesia. 8,9 We present a case of a Cesarean delivery, under general anesthesia using remifentanil, in a parturient with Marfan's syndrome and aortic root dilatation. The patient gave written, informed consent for the publication of this information, in accordance with our local institutional guidelines.…”
Section: Conclusion : Les Changements Hémodynamiques Pendant Le Péripmentioning
confidence: 99%
“…Placental malperfusion is the primary cause of fetal death and occurs when the intimal flap progresses to the internal iliac artery leading to uterine artery insufficiency. 11 Zeebregts et al 2 recommended a caesarian section at the time of operative repair only Ͼ28 weeks of gestation, but with the advances in neonatal management during the last decade, caesarian section earlier in pregnancy should be considered based on individual hospital neonatal experience and survival. …”
Section: Discussionmentioning
confidence: 99%